2012
DOI: 10.1021/om300159r
|View full text |Cite
|
Sign up to set email alerts
|

Tricarbonyl Mono- and Dinuclear Rhenium(I) Complexes with Redox-Active Bis(pyrazole)–Tetrathiafulvalene Ligands: Syntheses, Crystal Structures, and Properties

Abstract: Two new bis(3,5-dimethylpyrazole)-substituted tetrathiafulvalene ligands, 2,6(7)-bis(methylthio)-3,7(6)-bis(3sulfanyl-3,5-dimethylpyrazole)tetrathiafulvalene (L 1 ) and 2,3-bis(methylthio)-6,7-bis(3-sulfanyl-3,5-dimethylpyrazole)tetrathiafulvalene (L 2 ), have been prepared and characterized. On the basis of the two ligands, three interesting rhenium(I) tricarbonyl mono-or dinuclear complexes, ClRe(CO) 3 (cis-L 1 ) (1), [ClRe(CO) 3 (trans-L 1 )] 2 (2), and [ClRe(CO) 3 (L 2 )] 2 (3), have been prepared and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…8a). 27 The latter was obtained in one step by the reaction of a mixture of cis and trans bis(pyrazole)-TTF ligands with Re(CO) 5 Cl. Their XRD analysis revealed that the TTF skeleton is bended in 15 and planar in metalla-ring 16.…”
Section: Rings and Cages Incorporating The Tetrathiafulvalene Corementioning
confidence: 99%
“…8a). 27 The latter was obtained in one step by the reaction of a mixture of cis and trans bis(pyrazole)-TTF ligands with Re(CO) 5 Cl. Their XRD analysis revealed that the TTF skeleton is bended in 15 and planar in metalla-ring 16.…”
Section: Rings and Cages Incorporating The Tetrathiafulvalene Corementioning
confidence: 99%
“…In this context, very few examples of coordination-driven redox-active self-assembled discrete structures have been described so far. Their constituting ligands are usually based on electro-deficient skeletons such as triazine [ 17 , 18 ] or perylene diimide [ 19 25 ] units and more rarely on oxidable fragments [ 26 , 27 ]. It has to be noted that the electro-activity can also be located on the metal complex [ 28 38 ] or on pendant units [ 39 43 ] instead of being centered on the side-walls.…”
Section: Introductionmentioning
confidence: 99%
“…This type of macrocyclic assembly has been observed with other TTF derivatives bearing peripheral nitrile, phosphine, pyrazole or pyridine moieties. [34][35][36][37][38][39] In particular, it is worth noting that a [2+1] metallamacrocycle has been described upon assembly of Co(hfac)2 (hfac = hexafluoroacetylacetonate) with an analogue of 1 incorporating a 2-pyridyl group and the longer ethylene spacer. [34] In this case, however, coordination of the metal cations involved the two binding units at the periphery of the same dithiol ring.…”
Section: Resultsmentioning
confidence: 99%